UTILIZING ENGLISH SONGS TO IMPROVE WRITING ABILITY IN WRITING DESCRIPTIVE TEXT OF THE SEVENTH GRADERS AT MTS MIFTAHUL ULUM MALANG - Ramdani, Novita (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: English song, writing descriptive, seventh graders of MTs Miftahul Ulum Malang.English as a foreign language in Indonesia is used as the education requirement. In countryside, English is considered as not important for peoples’ daily life, so that many people put aside English. Fortunately, government supports this by deciding English as compulsory subject. Suyanto (2009) states that low exposure of English can be one of the consideration that learners are categorized as Young Learners. Young learners of English need different treatment in order to mastered English as Foreign Language. One of the different treatment that can be utilized for young learners is English Song.This study aims to find out the use of song in improving students’ ability in writing descriptive text. Research design that is used in this study is Classroom Action Research with the seventh graders of MTS Miftahul Ulum Malang as the subject. In order to obtained information, researcher used five instruments; (1) Writing test, (2) Students’ participation checklist, (3) Teaching participation checklist, (4) Field notes, and (5) Questionnaire.This study shows that the used of English song can help students’ ability in writing descriptive text, in term of generating idea, gaining vocabulary, and also motivate students to learn English. It was shown by the result of writing test which was administered in the end of the implementation. With the minimum score 70, there are 83% students who can get score more than 70. In addition, the rest of the students who could not achieved the minimum score still can improve their writing ability for about 25%. This means that there were learning process happened during the implementation of English song as teaching media. It was also revealed by the result of students’ participation checklist that students’ participation during the implementation was more that 80%.Based on the result of the study, researcher suggested the teacher to use English song in teaching English, especially teaching writing. Teacher needs to considered  appropriate song for appropriate level of the students. Teacher also can use English song for other skill. Researcher also suggested the further researcher to do study of problem faced by the students and teacher in teaching and learning English through English song.